Waterbirds wintering at the Prespa lakes as revealed by simultaneous counts in the three adjoining littoral states - Catsadorakis, Giorgos; Aleks, Pellumb; Avramoski, Oliver; Bino, Taulant; Bojadzi, Andon; Brajanoski, Zarko; Fremuth, Wolfgang; Kazoglou, Yannis; Koutseri, Irene; Logotheti, Annita; Malakou, Myrsini; Nikolaou, Haris; et al. (Macedonian Journal of Ecology and Environment, 2013)
Lakes Prespa and Lesser Prespa are shared by Albania, Macedonia and Greece. Although situated at high altitudes they host notable numbers of wintering waterbirds. This paper presents results from simultaneous counts of wintering waterbirds in 2010-2012 carried out by researchers from the three adjoining littoral countries. The results are compared with those of almost simultaneous counts made in 1997-2000 as well as with older data in order to give the first complete account of the wintering birds at the Prespa lakes. Thirty bird species occurred regularly and another nine were observed irregularly. The six most numerous species were Common Coot Fulica atra, Great Crested Grebe Podiceps cristatus, Tufted Duck Aythya fuligula, Common Pochard Aythya ferina, Black-necked Grebe Podiceps nigricollis and Black-headed Gull Larus ridibundus. The first three made up over 80% of all wintering birds. The average number of wintering waterbirds for the period 2010-2012 was 39,089, 16% less than the average number of the previous period (1997-2000) which was 46,993 birds. Total numbers of wintering birds present at the lakes in 2010-2012 ranged from 36,260 to 45,412, and were dominated by Common Coot, which comprised 61.5 % of all birds, compared to 53% in 1997-2000. Overall numbers of coots remained stable at around 24,500 individuals. Great Crested Grebe, the second most common species, showed a decline of ca 32% and a partial shift in distribution from Greece to Macedonia and the overall numbers of Black-necked Grebe, Tufted Duck and Common Pochard decreased compared to the earlier period. The mean number of wintering waterbirds at the two Prespa lakes by far exceeds the Ramsar criterion (20,000 individuals) and thus the lakes qualify as a wetland of international importance.